Article Review of The Critical and Empirical Research in Islamic Economics - Brahim Achour; Ibrahim Foughali; Liya Ur Rahman Liyakath Alikhan; Nur Jamaludin (STES Islamic Village, 2020)
Abstract This article depicts the nature scope and methodology of reconstruction of Islamic economics as well as it speaks about possibilities on theoretical and empirical research in this field. The article also intends to revel needy of reconstruction of Islamic economics, and its role in early stage and contemporary period and how it would be in future. Islamic economics through the shade of quran and sunnah clearly mandate about allocation of resources, goods and services as well distribution of output, input and wealth in an economy. It is also giving the solution for the problems such as financial crises, poverty, inflation, economic inequalities and unemployment. In addition, methodologically, description of the ground realities and prescription of solutions for economic issues are concern of Islamic economics, whereas, field of fiqh plays massive role in developing of Islamic economics. Theoretically, this article discusses about Islamic economics theory and its advantages, this includes Islamic economic system, Shari’ah based transaction matrix, institutional matters, etc. on the empirical side, there are some points affiliated with data and empirical works are discussed.